The Effect of Combination Avocado Juice Administration and Storytelling Therapy on Body Weight in Children with HIV/AIDS - Warsini, Warsini; Ariasti, Dinar (Indonesian Journal of Medicine, 2020)
Background: The incidence of HIV/AIDS is increasing. In 2015 there were 30,935 new cases, 41,250 in 2016 and 33,660 in 2017, where new case findings were also found in children aged less than 4 years and caused child deaths worldwide in 2011 to reach 230,000. At present there is no treatment that can cure the disease, so various efforts are made to support the health and quality of life of sufferers. The purpose of this study was to analyze the effect of providing a combination of avocado juice and storytelling therapy on the weight of a child with HIV / AIDS.Subjects and Method: This was a quasy-experimental with pre-post test design. A sample of 15 children with HIV/AIDS was selected for this study. The dependent variable was body weight. The independent variable was a combination of avocado juice and storytelling therapy. Weight data was measured using weight scales. Data were analyzed using the Wilcoxon test.Results: Body weight (kg) after intervention (Mean= 26.17; SD= 9.30) was slightly greater than before intervention (Mean= 25.30; SD= 9.16), with p= 0.002.Conclusion: Combination of avocado juice and storytelling therapy increased body weight in children with HIV/AIDS.Keywords: storytelling therapy, avocado juice, children with HIV/AIDSCorrespondence: Warsini. Nursing Academy of Panti Kosala, Surakarta, Central Java. Alamat Instansi Jl. Raya Solo-Baki KM. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: warsinimulyono@gmail.com. Mobile: 0816418071Indonesian Journal of Medicine (2020), 05(02): 148-152https://doi.org/10.26911/theijmed.2020.05.02.09